Prospects for the Regulation of Harmful Substances Produced by the Oil Production Enterprise: Prospek Regulasi Zat Berbahaya yang Dihasilkan oleh Perusahaan Produksi Minyak - Keldiyarova Gulmira Farkhadovna; Otakulov Bekzod Nuriddinovich; Boymurodova Xushidabonu Qudratullayevna (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the identification, quantification, and regulatory aspects of pollutant sources in an oil production joint venture. The research aims to determine the number of sources and quantify the substances released, while analyzing regulatory frameworks addressing harmful emissions. Employing a multifaceted approach, we utilize advanced methods for source identification and quantify emitted substances. Results reveal key sources and their associated emission levels, shedding light on the environmental impact of the joint venture. The implications of our findings extend to refining regulatory strategies for mitigating adverse effects on the environment, making this study crucial for global scientists and policymakers alike. Highlights: Comprehensive Assessment: This study provides a thorough examination of pollutant sources in an oil production joint venture, offering a detailed understanding of the various contributors to environmental contamination. Quantification and Identification: Advanced methods are employed to quantify the number of pollutant sources and identify the substances released, providing precise data crucial for regulatory considerations and environmental management. Regulatory Implications: The research analyzes existing regulatory frameworks addressing harmful emissions, suggesting potential improvements to enhance environmental protection and promote sustainable practices in oil production joint ventures. Keywords: Pollutant Sources, Oil Production, Joint Venture, Permitted Rate, Environmental Condition.